1996
DOI: 10.1080/15513819609168704
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fibrosing Pancreatitis in Childhood: Report of a Case and Literature Review

Abstract: Chronic fibrosing pancreatitis in childhood is an uncommon condition of unknown etiology with a variety of clinical presentations, histopathologic features, and outcomes. The diagnosis is one of exclusion (of hereditary or secondary pancreatitis), which should include histological assessment. The histological features of this condition have been described, to our knowledge, in nine published cases. We report a case in a 13-year-old male, who presented with obstructive jaundice and subsequently had evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The presentation of our patient with abdominal pain and obstructive jaundice was similar to the presentation of 25 (54%) of the reported cases of this disorder [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Most of the cases reported (36/46, 78%) presented with abdominal pain, discomfort, or cramping, with or without jaundice.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The presentation of our patient with abdominal pain and obstructive jaundice was similar to the presentation of 25 (54%) of the reported cases of this disorder [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Most of the cases reported (36/46, 78%) presented with abdominal pain, discomfort, or cramping, with or without jaundice.…”
Section: Discussionsupporting
confidence: 74%
“…Dilated CBD and gallbladder Chronic inflammation, severe fibrosis Little et al [25] Not reported Not reported Stephen et al [11] Enlarged, hard pancreas; liver green and smooth Diffuse fibrosis and inflammation including acini Barkin et al [3] Nodular hard pancreas in both cases 1 diffuse fibrosis with relative sparing of acini 1 not reported Amerson and Ricketts [12] 2 patients: hard mass at head of pancreas 4 chronic fibrosing pancreatitis 2 patients: diffuse fibrosis of pancreas Lewin-Smith et al [13] Enlarged, indurated, fibrotic pancreas. Dilated biliary tree Chronic sclerosing pancreatitis with active destruction of glands Sylvester et al [14] 2 patients: stent placement and no surgery 3 extensive fibrosis 2 patients: hard, fibrotic pancreas 1 evident islet cells Seino et al [26] No surgery Not reported Keil et al [16] Whole pancreas hard mass Severe fibrosis, some acinar tissue and several islet cells Sclabas et al [15] Not reported Fibrosis…”
mentioning
confidence: 99%
“…The outcome of these three cases was not different from those children reported in the literature treated surgically [1,3,9,17]. It appears that the natural history of fibrosing pancreatitis is to progress from pancreatic enlargement (which may be more focal in the head of the gland) to atrophy.…”
Section: Discussionmentioning
confidence: 64%
“…Diabetes mellitus is unusual, and any impairment of glycemic control tends to be mild. There are no reports of long-term follow up in this condition [9,16], but one of our patients (case 1) has now been under review for 3 years and remains well despite the continued need for pancreatic enzyme supplements. We are also aware (authors' experience) of a case that presented 14 years ago at the age of 6 years with a similar picture and was managed with a surgical drainage procedure (cholecystostomy).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation